Development of heart failure in young patients with congenital heart disease: a nation-wide cohort study - Annika Rosengren; Mikael Dellborg; Thomas Gilljam; Zacharias Mandalenakis; Georgios Lappas; Peter Eriksson; Kristofer Skoglund (Open Heart)
Objective Heart failure (HF) is a common cause of hospitalisation and death in adults with congenital heart disease (CHD). However, the risk of HF in young patients with CHD has not been determined.Methods By linkage of national patient registers in Sweden, we identified 21 982 patients with CHD born between 1970 and 1993, and compared these with 10 controls per case. Follow-up data were collected from birth until 2011 or death.Results Over a mean follow-up of 26.6 years in patients with CHD and 28.5 years in controls, 729 (3.3%) and 75 (0.03%) developed HF, respectively. The cumulative incidence of HF in all CHD was 6.5% and in complex CHD 14.8% up to age 42 years. Thus, one patient in 15 with CHD runs the risk of developing HF before age 42 years, a risk that is 105.7 times higher (95 % CI 83.2 to 134.8) compared with controls. For patients with complex CHD (such as conotruncal defects, univentricular hearts, endocardial cushion defects), one in seven will develop HF, a HR of 401.5; 95% CI 298 to 601 as compared with controls. The cumulative probability of death in patients with CHD, after HF diagnosis, was 63.4% (95% CI 57.5 to 69.3).Conclusions An extremely high risk of developing HF (more than 100-fold) was found in patients with CHD, compared with matched controls, up to the age of 42 years. Patients with complex congenital heart malformations carried the highest risk and have to be considered as the main risk group for developing HF.